Training system for converting current visual information to bird’s-eye view - Sumi, Kaoru; Okuyama, Ryo (Frontiers in Psychology, 2024)
IntroductionEffective decision-making in ball games requires the ability to convert positional information from a first-person perspective into a bird’s-eye view. To address this need, we developed a virtual reality (VR)-based training system designed to enhance spatial cognition.MethodsUsing a head-mounted virtual reality display, participants engaged in tasks where they tracked multiple moving objects in a virtual space and reproduced their positions from a bird’s-eye perspective. The system simulated game-like scenarios to systematically train this cognitive skill. Participants’ performance was assessed before and after the training.ResultsThe experimental results revealed significant improvements in spatial accuracy and cognitive ability among participants after using the system. These enhancements were measured by their ability to accurately convert first-person positional data into a bird’s-eye perspective.DiscussionThe findings suggest that the VR-based system effectively enhances perceptual-cognitive skills critical for team sports and other tasks requiring advanced spatial awareness. This training method holds potential for broader applications in spatially demanding activities.